The Influence of Boarding School Life on The Spiritual Development of Female Students - Sianipar, Joseph; Tarigan, Nuren (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2024)
This study aims to determine the effect of life in a boarding school on the spiritual development of female students. This study was conducted at the SLA-UASN campus in the 2023-2024 Academic Year. This type of research is quantitative. Data sources were obtained by distributing questionnaires to female students living in the SLA-UASN girls dormitory. The population in this study consisted of 132 female students and the number of junior high/high schools was 58, and the Special Dormitory was only 18 people. With the probability sampling technique, a sample of 70 female students living in the SLA-UASN female dormitory was obtained. The analysis technique used was a simple linear regression analysis technique. The results of this study indicate that life in a boarding school (X) has a positive and significant effect on the spiritual development (Y) of female students at the SLA UASN campus in the 2023-2024 Academic Year. life in a boarding school can have an influence of 70.6% on spiritual development.